2015
DOI: 10.1111/ppl.12349
|View full text |Cite
|
Sign up to set email alerts
|

Two WUSCHEL‐related HOMEOBOX genes, PeWOX11a and PeWOX11b, are involved in adventitious root formation of poplar

Abstract: The plant-specific WUSCHEL-related HOMEOBOX (WOX) transcription factors play important roles in key developmental processes, but knowledge regarding functional characterization of WOX genes in poplar remains limited. To reveal genes and signaling pathways associated with adventitious rooting in poplar, here we isolated and characterized two WOX genes through the rapid amplification of cDNA ends (RACE), sequence aligning, expression profiling, protoplast transfection and poplar transformation. Detailed informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 39 publications
(59 reference statements)
2
53
1
Order By: Relevance
“…The Populus (cultivar ‘Nanline895’) genome contains two WOX11 paralogs: PeWOX11a and PeWOX11b . Xu et al () found that constitutive overexpression of PeWOX11 in transgenic lines not only enhanced the rate of rooting, but also increased numbers of ARs per cutting. In conclusion, the closely related homologs of AtWOX11 in rice and Populus are required for proper AR formation, suggesting that WOX11 likely mediates a conserved evolutionary mechanism of adventitious rooting in monocots and dicots, including woody species (Zhao et al , Xu et al ).…”
Section: Auxin: the Master Player And Hub Of Any Crosstalkmentioning
confidence: 99%
“…The Populus (cultivar ‘Nanline895’) genome contains two WOX11 paralogs: PeWOX11a and PeWOX11b . Xu et al () found that constitutive overexpression of PeWOX11 in transgenic lines not only enhanced the rate of rooting, but also increased numbers of ARs per cutting. In conclusion, the closely related homologs of AtWOX11 in rice and Populus are required for proper AR formation, suggesting that WOX11 likely mediates a conserved evolutionary mechanism of adventitious rooting in monocots and dicots, including woody species (Zhao et al , Xu et al ).…”
Section: Auxin: the Master Player And Hub Of Any Crosstalkmentioning
confidence: 99%
“…Subsequently, a transcription factor in the AP2 family was also found to play a role during AR formation [28]. Several WUSCHEL-related HOMEOBOX (WOX) transcription factors have also been reported to regulate key developmental processes in AR formation in poplar [29,30]. However, there is still insufficient understanding of poplar AR formation compared with that of AR formation in herbaceous model plants.…”
Section: Introductionmentioning
confidence: 99%
“…An ideal RG should be stable expressed in different tissue types, development stages and under different experimental conditions. Then, housekeeping genes involved in basic cellular processes are used as representative of the traditional internal RGs in many studies, such as ACT ( Actin ), TUB ( Tubulin ), 18S ( 18S ribosomal RNA ), UBC ( Ubiquitin-conjugating enzyme ), EF1 α ( Elongation factor-1 alpha ) ( Fiume and Fletcher, 2012 ; Mousavi et al, 2013 ; Sakuraba et al, 2014 ; Tian H. et al, 2015 ; Xu et al, 2015 ; Liu et al, 2016 ). However, many studies also show that housekeeping genes have been not stably expressed under any tissues and all experimental conditions ( Schmittgen and Zakrajsek, 2000 ; Jain et al, 2006 ; Hong et al, 2008 ; Wang et al, 2014 ; Xu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%